Pretočni režimi v Sloveniji med letoma 1971 in 2000 - Frantar, Peter (Geografski vestnik, 2005)
This paper provides a statistical analysis of monthly discharge coefficients at 43 water gauging stations on 35 Slovenian rivers. The coefficients were calculated based on data for the average monthly discharge over the years from 1971 to 2000. Using cluster analysis, five types of discharge regimes were identified. A comparison of the results obtained for this period with the findings of similar studies for the period 1961-1990 confirms the powerful impact of climate changes in the last decade of the 20th century. By means of a t-test we found statistically significant differences in the ten-year averages for montly discharge coefficients.
Keywords: hidrogeografija; reke; rečni režim; vodni režim; klimatske spremembe; podnebne spremembe; Slovenia; Slovenija